Isolated brain metastasis from prostate cancer: A case report - Abhijit Singh; Amit Tuli; Kim Jacob Mammen (CHRISMED Journal of Health and Research, 2018)
Brain metastases arising from prostate cancer are exceedingly rare and generally occur late in the course of the disease. Most patients have widespread metastatic disease before developing brain metastases from prostate cancer. We report the case of an 80-year-old male with adenocarcinoma of the prostate presenting with isolated symptomatic brain metastasis.